Clinical efficacy of peripheral blood mononuclear cell secretome application in patients with repeated implantation failure - Obedkova, Kseniia V.; Ryzhov, Julian R.; Storozheva, Kseniia V.; Khalenko, Vladislava V.; Safarian, Galina Kh.; Savicheva, Alevtina M; Budilovskaya , Olga V.; Krysanova, Anna A.; Gzgzyan, Aleksandr M.; Bespalova, Olesya N.; Tapilskaya , Natalya I. (Acta Biomedica Atenei Parmensis, 2024)
Abstract. Background and aim: Recurrent implantation failure (RIF) and recurrent pregnancy loss (RPL) are significant challenges in reproductive medicine, often linked to endometrial dysfunction and chronic endometritis (CE). Current treatments, including antibacterial therapies, are not always effective. This study aims to evaluate the clinical efficacy of peripheral blood mononuclear cell (PBMC) secretome in enhancing endometrial receptivity and improving pregnancy rates in patients with RIF associated with CE. Methods: At present, the researches for alternative agents for the complex treatment of chronic endometritis are conducted. One of the promising options is the introduction of peripheral blood mononuclear cell (PBMC) secretome containing a variety of biologically active substances, including proteins, extracellular vesicles, antimicrobial peptides, nucleotides, lipids, interleukins and cytokines necessary for endometrial receptivity enhancement in patients with chronic endometritis and infertility. A total of 54 women with long-term infertility were enrolled and divided into two groups: the main group receiving PBMC secretome and a comparison group undergoing standard antibacterial therapy. The PBMC secretome was prepared from cultured PBMCs, and its biological activity was assessed Results: In our study, the pregnancy rate in patients with long-term infertility after PBMC secretome administration was significantly higher when compared to women after antibacterial therapy Conclusions: The application of PBMC secretome appears to enhance reproductive outcomes in women with RIF due to CE. These findings support the potential of PBMC secretome as a novel therapeutic option for improving endometrial health and warrant further investigation in larger clinical trials. (www.actabiomedica.it)